A cross-sectional study to assess job strain of emergency healthcare workers by Karasek questionnaire: The SEEK study - Bouillon-Minois, Jean-Baptiste; Trousselard, Marion; Mulliez, Aurélien; Adeyemi, Oluwaseun John; Schmidt, Jeannot; Thivel, David; Ugbolue, Ukadike Chris; Borel, Marjolaine; Moustafa, Farès; Vallet, Guillaume T.; Clinchamps, Maëlys; Zak, Marek; et al. (Frontiers in Psychiatry, 2023)
Background: Emergency healthcare workers (eHCWs) are particularly at risk of stress, but data using the gold standard questionnaire of Karasek are scarce. We assessed the level of stress of eHCWs, and aimed to compare with general population. Methods: Cross-sectional nationwide study in French Emergency Departments, using the job-content questionnaire of Karasek, compared with the 25 000 answers in French general population (controls from the SUMER study). Description of job demand, job control and social support were described as well as prevalence of jobstrain and isostrain. Putative factors were searched using mixed-method analysis Results: 166 eHCWs (37.9±10.5 years old, 42% men) from five French Emergency Department were included: 53 emergency physicians and 104 emergency paramedics, compared to 25 000 workers with other occupations. Job-demand was the highest for physicians (28.3±3.3) and paramedics (25.9±3.8), compared to controls (36.0±7.2) (p<0.001). Job-control was the lowest for physicians (61.2±5.8) and paramedics (59.1±6.8), compared to controls (70.4±11.7) (p<0.001). Mean social support did not differ between groups (23.6±3.4 for physicians, 22.6±2.9 for paramedics, and 23.7±3.6 for controls). The prevalence of job-strain was massively higher for physicians (95.8%) and paramedics (84.8%), compared to controls (23.9%) (p<0.001), as well as for isostrain (45.1% for physicians, 56.8% for paramedics, and 14.3% for controls, p<0.001). We did not find any significant impact of sociodemographic on job control, job demand or social support. Conclusion: eHCWs have a dramatic rate of jobstrain, necessitating urgent promotion of policy to take care of them.